THE USE OF QUESTION ANSWER–RELATIONSHIP (QAR) STRATEGY ON IMPROVING STUDENTS’ READING COMPREHENSION - Жидебаева, Д.Б. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The abstract discusses a strategy that addresses the challenge of reading comprehension among senior high school students. It uses the Question–Answer Relationship (QAR) strategy to help students understand narrative texts better. The QARstrategy training is effective, leading to improved comprehension, increased student engagement, and greater confidence in answering questions. Overall, it highlights the positive impact of using the QAR strategy in the classroom.
Keywords: QAR strategy; strategy training; reading comprehension; narrative text